Construction of a polyMOF using a polymer ligand bearing the benzenedicarboxylic acid moiety in the side chain. (10th March 2020) - Yazaki, Kohei; Takahashi, Masaki; Miyajima, Naoya; Obata, Makoto
Abstract : Here we report a new synthetic strategy of a polyMOF consisting of a side chain ligand polymer. The polyMOF was consisting of a crystalline MOF-like structure in the polymer despite its film form. Abstract : The design and synthesis of several types of metal–organic frameworks (MOFs) have been extensively reported in literature. However, the construction of MOFs using a polymer ligand (polyMOF) is still an emerging field of research. This work reports a new molecular synthetic design strategy to produce a polyMOF composed of polymer ligands with a benzenedicarboxylic acid moiety in the side chain. Powder X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy techniques were used to confirm the structures of the resulting polyMOF. Despite the film shape obtained, the resulting Zn-polyMOF showed crystalline structures, per the microscopy images obtained during powder X-ray diffraction.